Nanotechnology applied to drug development: an integrative literature review (Research, Society and Development, 2022)
Nanotechnology is a field of science responsible for studies on structured systems at the nanometer scale. In the pharmaceutical field, nanocarriers have been investigated as a vehicle for drugs in the synthesis of innovative drugs to solve difficulties regarding bioavailability, stability, and toxicity. Nanostructured pharmaceutical formulations are able to control the release of molecules and also direct these molecules to their specific site of action and thus maximize the beneficial effects of therapy, as well as assist in reducing adverse effects. Several studies have shown excellent results in the therapeutic efficacy of nanocarriers used in the development of new drugs. Moreover, these nanopharmaceuticals offer numerous advantages when compared to conventional pharmaceutical forms. The present work aims to perform an integrative literature review on the employability of nanotechnology in the development of new drugs, discussing the main nanocarriers that can be used to obtain drugs, such as liposomes, polymeric nanoparticles, lipidic nanoparticles, dendrimers, and cyclodextrins. Thirty-one articles were used that passed the inclusion criteria, which required academic articles with the language in Portuguese, English, Spanish and Chinese, published in the last five years retroactively. In view of the studies carried out by the authors, it is concluded that nanotechnology when applied to the production of drugs is very efficient because it allows a significant improvement in their pharmacokinetic properties, resulting in a safe and effective treatment to the patient.